Predictors of care burden among caregivers of patients with COVID‐19 - Maryam Janatolmakan; Armin Naghipour; Shahab Rezaeian; Alireza Khatony (Wiley, 2023)
Abstract Aim To explore predictors of care burden among the caregivers of patients with COVID‐19. Design The findings of this cross‐sectional study were presented in accordance with the guidelines outlined in the Strengthening the Reporting of Observational Studies in Epidemiology statement. Methods The samples included 172 caregivers in Imam Reza and Farabi Hospitals, located in Kermanshah, Iran, who were enrolled in the study using convenience sampling. A demographic information form and the Caregiver Burden Inventory were administered. The data were collected between 13 May 202 and 20 August 2021. Results Of the caregivers, 62.8% (n = 108) were male and 71.5% (n = 123) were over 40 years old. Furthermore, 66.3% (n = 114) of caregivers had severe and very severe care burden, with a mean care burden of 78.9 ± 20.4 out of 120. A statistically significant difference was found between care burden and the variables of monthly income, health status, number of patients under care and residence status (p < 0.05). Conclusion The caregivers experienced a high care burden, which can have harmful effects on them. Therefore, it is necessary to provide them with various forms of economic, psychological and social support.